Wealth doesn't last 3 generations : how family businesses can maintain prosperity - Lee, Jean (Jean S. K.) (World Scientific, 2009)
In this book, three modern Chinese family businesses, including food and beverage company Yeo Hiap Seng, are studied to analyze the problems that family enterprises face. Other case studies include long-standing family businesses in Europe, America and Asia, such as Ford, Kikkoman and Samsung. This book also discusses the changing characteristics of Chinese family businesses, the pitfalls that such enterprises are likely to face, and how they can overcome these pitfalls and achieve sustainable development.